All‐Cellulose‐Based Quasi‐Solid‐State Sodium‐Ion Hybrid Capacitors Enabled by Structural Hierarchy. (17th July 2019) - Xu, Zhen; Xie, Fei; Wang, Jing; Au, Heather; Tebyetekerwa, Mike; Guo, Zhenyu; Yang, Shengyuan; Hu, Yong‐Sheng; Titirici, Maria‐Magdalena
Abstract: Na‐ion hybrid capacitors consisting of battery‐type anodes and capacitor‐style cathodes are attracting increasing attention on account of the abundance of sodium‐based resources as well as the potential to bridge the gap between batteries (high energy) and supercapacitors (high power). Herein, hierarchically structured carbon materials inspired by multiscale building units of cellulose from nature are assembled with cellulose‐based gel electrolytes into Na‐ion capacitors. Nonporous hard carbon anodes are obtained through the direct thermal pyrolysis of cellulose nanocrystals. Nitrogen‐doped carbon cathodes with a coral‐like hierarchically porous architecture are prepared via hydrothermal carbonization and activation of cellulose microfibrils. The reversible charge capacity of the anode is 256.9 mAh g −1 when operating at 0.1 A g −1 from 0 to 1.5 V versus Na + /Na, and the discharge capacitance of cathodes tested within 1.5 to 4.2 V versus Na + /Na is 212.4 F g −1 at 0.1 A g −1 . Utilizing Na + and ClO4 − as charge carriers, the energy density of the full Na‐ion capacitor with two asymmetric carbon electrodes can reach 181 Wh kg −1 at 250 W kg −1, which is one of the highest energy devices reported until now. Combined with macrocellulose‐based gel electrolytes, all‐cellulose‐based quasi‐solid‐state devices are demonstrated possessing additional advantages in terms of overall sustainability. Abstract : All‐cellulose‐based quasi‐solid‐state sodium‐ion hybrid capacitors are assembled based on hierarchically structured carbon materials inspired by multiscale building units of cellulose as well as cellulose‐based gel electrolytes. The kinetics of the electrochemical reactions inside the hybrid capacitors are studied to bridge the gap between batteries (high energy) and supercapacitors (high power).